GLYCATIVE AND LIPOXIDATIVE STRESS BIOMARKERS CORRELATION WITHADVANCED DIABETIC NEPHROPATHY - Hama Faraj, Amna M. Salih; Salih, Burhan Ahmed Salih (Science Journal of University of Zakho, 2026)
Diabetic nephropathy (DN) is the leading cause of end stage kidney disease (ESKD). Among the factors that contribute to DN are inflammation and hyperglycemia induced oxidative stress. This case-control study examined serum levels of OS biomarkers, advanced glycation end products (AGEs) and oxidized low-density lipoprotein (ox-LDL), in 60 stage five chronic kidney disease (CKD) patients versus 60 healthy controls. The biochemical parameters that were assessed include, creatinine, urea, eGFR, Hba1c, fasting blood glucose, albumin, and electrolytes. DN patients exhibited loss of kidney function (eGFR: < 15mL/min/1.73m2; creatinine: 6-10 mg/dL; urea: 140-170 mg/dL), poor glycemic control (Hba1c: 6-8%; fasting glucose: 310-390 mg/dL), and low calcium and albumin levels (calcium: 9 to 9.8 mg/dL; albumin: 3.1 to 3.9 g/dL) compared to healthy controls. Electrolytes (sodium, potassium, and chloride) showed no significant differences due to dialysis correction. DN patients exhibited AGEs serum levels ranging from 3000 to 3300 ng/mL (p = 0.0009) and ox-LDL levels ranging from 27 to 30 ng/mL (p < 0.0001), that were significantly elevated compared to healthy controls, confirmed heightened OS. The high AGE levels contribute to DN through the induction of basement membrane thickening, fibrosis and inflammation leading to further podocyte injury. While high Ox-LDL levels induce endothelial dysfunction and inflammation contributing to nephron loss. These findings implicate AGEs and ox-LDL as key contributors to DN progression through tissue damage, inflammation, and lipid peroxidation. Their significant elevation in advanced DN highlights their potential as predictive biomarkers and therapeutic targets in CKD.